Pengaruh Gaya Kepemimpinan, Motivasi, dan Promosi Karyawan terhadap Kinerja Karyawan pada PT. PLN (Persero) ULP Porong - Nugroho, Mukhamad Aditya Bayu; Kusuma, Kumara Adji; Abbadiyah, Rifdah (Universitas Nusantara PGRI Kediri, 2024)
The purpose of this study is to analyze, identify and show the influence of training, career development, and motivation on employee performance at PT. PLN (Persero) Porong. The method used in this study is to use a quantitative research approach with primary data sources. This study used 100 respondents from a sample of PT. PLN (Persero) Porong employees. The analysis technique used multiple linear regression analysis, classical assumptions, partial tests (t-test), simultaneous tests (f-test), and hypothesis testing using the coefficient of determination. Data processing in this study used the Statistical Program for Social Science (SPSS) version 26, Data collection techniques used a questionnaire with a Likert scale and sampling techniques used purposive sampling. The results of this study partially showed that leadership style, motivation, and employee promotion had a positive and significant effect on employee performance, and simultaneously had a positive and significant effect together.